(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The structural model of the family organization of the educational space of a child with special needs is substantiated, which acts as the manager in the process of integrating the child into the general educational environment and consists of three components: the social and educational space (specialized programs), the home educational space and the inclusive formal educational space. Proved that the general socio- psychological conditions including a child with special needs in general education area are: general social attitudes in education; willingness educational institutions (formal, postformal and informal) to work with inclusive children; professional and educational specialists of social areas to work with children with special needs; parental settings on inclusion and the child’s high level of education; level of social competence and psychological readiness of the child to inclusion; social support for families. The "Program of socio-psychological support of families in which children with special educational needs are brought up" is developed, on the one hand, corresponds to social demand and social basic attitudes, and on the other hand to the individual psychological characteristics of the child. Thanks to its implementation, it was possible to change the parents’ attitudes towards the education of their children; increase the level of the child’s psychological preparedness for learning; to form a clear awareness of the importance and role of social support for families raising a child with special needs in the professional work of specialists in social work.